Painting greeting cards for fun & profit - Robertson, Jeanette (Cincinnati, Ohio : North Light Books, 1999)
Picture your painting on the front of a greeting card, ready to brighten someone's day. You can make it happen! This book shows you not only how to create beautiful cards, but how to sell them, too. To help you get started, Jeanette Robertson and a dozen other successful greeting card artists share what they've learned
Includes index.
Keywords: Greeting cards -- Marketing; Tradeshows -- Marketing